Analysis of the Nutritional Content of Catfish Extract as a Reliable Food Ingredient to Improve the Nutrition of Stunted Toddlers - Sihombing, Ferdinan; Rumaseuw, Ellen Stephanie; Raniadita, Maria Alfa (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Stunting is one of the focuses of the Sustainable Development Goals (SDGs), which includes the secondary goal of ending hunger and all forms of malnutrition. Stunting is a serious chronic nutritional problem throughout the world, especially in developing countries. Stunting occurs when a child does not get enough nutrition during his growth period and can result in impaired physical growth and cognitive development. An effective solution to overcome stunting is to increase your intake of protein and important nutrients through additional food. Catfish has been proven to be a potential nutritional raw material for overcoming stunting because it is rich in protein and nutrients. The aim of this research is to analyze in detail the nutritional content of catfish extract which is considered a superior food ingredient for overcoming stunting. This research used a purposive sampling method by measuring proximate tests, total polyphenols and antioxidant activity (DPPH). It is hoped that the results of this research will provide further insight into the nutritional value of catfish extract and its potential in improving the nutritional status of stunted children. The results showed that catfish extract had a water content of 4.97%, ash content of 8.91%, fat content of 29.87%, protein content of 48.85%, carbohydrate content of 7.40%, total polyphenol content of 0.12% and antioxidant activity with an IC50 value of 4.9724%. This research concludes that catfish extract has the potential to improve nutrition for stunted toddlers.